Magnetic Fields of Devices during Electric Vehicle Charging: A Slovak Case Study - Iveta Marková (MDPI AG, 2021)
The aim of this contribution is to identify and quantify the magnetic field parameter (MP) devices for charging electric vehicles (EVs). An EV is a mobile device. The EV remains a mobile device even when it is charging in a fixed charging stand. ICNIRP and SBM standards apply to stable devices. A magnetic field (MF) creates local gradient fields that change cyclically over time near the charging stations. The rotating vector MF is a specific parameter. An MF is evaluated by its strength and spatial changes. The triaxial fluxgate magnetometer VEMA-041 was used for the measurements. The MF was observed in the frequency range of 0–250 Hz, and the magnetic induction density was from T 2 × 10−9 T to 2 × 10−5 T, with a sensitivity of 1.7 nT. The MF analysis was performed within the time and frequency range. The rotating vector MF was identified at the measurement points. Measurements were realized for the charge under the following parameters: cables, 600 A; transformer, 250 kVA (22 kV/400 V); a cab-fixed charging stand, and an AC/DC charger in the EV. EV charging was performed with 6.6 kW of power and 43-kW fast charging. The measured results were satisfactory, according to the ICNIRP and SBM 2015 standard. The values measured at a distance of 1 m from the wall of the transformer were BRMS < 2 µT. BRMS values < 3 µT were measured in the space of the cable’s entry into the distribution box. EV values should not be assessed under this regulation. However, an EV is a mobile device. In the selected EV sample (a first-generation Nissan Leaf), a frequency of 10 Hz and its multiples were detected during charging. The frequencies were generated in an AC/DC charger in the EV. These frequencies reached BRMS < 0.2 µT in the driver’s footwell. The maximum value of the MF rotating vector was Btotal < 0.3 µT and was directed to the crew area of the EV. The AC/DC charger generated BRMS = 0.95 µTin the driver’s footwell. It is necessary to look for new tools for evaluating MFs for EVs, such as the standards used for stable sources today. These standards should be based on dosimetric principles.